\begin{align}
0 & =\emptyset\\
a_{0}(0,0) & = 1 = \{0\}=0^+\\
a_{0}(0,1) & = 1\\
S & =\{1,a_{0}(0,3),a_{0}(0,5)\}\\
n > 0: a_{0}(0,n+1) & = a_{0}(a_{0}(0,n),S) \\
a_{m+1}(0,n+1) & = a_m(a_{m+1}(0,n),S) \\
a_{0}(0,\omega) & = \sup(a_{0}(0,n)|n\in \Bbb{N})\\
a_{m}(\omega,\omega) & = \sup(a_{m}(\omega,n)|n\in \Bbb{N})\\
a_{1}(\omega,0) & = a_{0}(0,\omega)\\
a_{m}(\omega,1) & = a_{0}(0,\omega)\\
a_{m+1}(\omega,2) & = a_{m}(\omega,\omega)\\
a_{1}(a_{m}(\omega,n),0) & = a_{m}(\omega,n)\\
m>q>1: a_{q}(a_{m}(\omega,n),1) & = a_{m}(\omega,n)\\